Kerjasama Jepang dan Indonesia - Seniwati; Munif Arif Ranti; Oktaviano Nandito Guntur; Ibnu Aly Badiu (Department of International Relations, Hasanuddin University, 2021)
This article focuses on the cooperation between Japan and Indonesia. At the beginning of the article, we discussed the development of the Japanese economy after World War II. The Japanese economy collapsed after World War II. However, in the 1960s and 1980s, Japan had become the highest-paid economy. Japan develops technology and builds human resources by focusing on their social infrastructure and social traditions. Japan does not take funds from abroad to support its economic and technological development. Japan prefers to cooperate with local industry and social infrastructure development. Japan continues to build its education system and develop the business culture that has become their tradition. Indonesia and Japan have long established cooperation. The two countries cooperate in almost all sectors such as economic, cultural, social, and security. One form of bilateral cooperation that has been implemented is the Indonesia-Japan Economic Partnership Agreement (IJEPA). Indonesia is Japan's biggest development partner. Japan's overseas development assistance (ODA) has supported Indonesia's infrastructure, agriculture, industry, education, health and social development as well as institutional and capacity building. Artikel ini berfokus pada kerjasama Jepang dan Indonesia. Pada awal artikel, kami membahas perkembangan ekonomi Jepang setelah Perang Dunia II. Perekonomian Jepang hancur setelah terjadinya Perang Dunia II. Meskipun demikian, pada era tahun 1960an hingga 1980an, Jepang telah menjadi ekonomi dengan berupah tertinggi. Jepang mengembangkan teknologi dan membangun sumber daya manusia dengan berfokus pada infrastruktur sosial dan tradisi sosial mereka. Jepang tidak mengambil dana dari luar negeri untuk mendukung pembangunan ekonomi dan teknologinya. Jepang lebih memilih untuk menjalin kerja sama dengan industri lokal dan pembangunan infrastruktur sosial. Jepang terus membangun sistem pendidikannya dan mengembangkan kultur bisnis yang telah menjadi tradisi mereka. Indonesia dan Jepang sudah lama menjalin kerja sama. Kedua negara menjalin kerjasama hampir disemua sektor seperti ekonomi, kebudayaan, sosial, dan keamanan. Salah satu bentuk kerja sama bilateral yang telah terlaksana seperti Indonesia-Japan Economic Partnership Agreement (IJEPA). Indonesia merupakan mitra pembangunan terbesar bagi Jepang. Bantuan pembangunan luar negeri Jepang (ODA) telah mendukung pembangunan infrastruktur, pertanian, industri, pendidikan, kesehatan dan sosial Indonesia serta pembangunan kelembagaan dan kapasitas.